Study the Effect of Substitution Filler on performance of Asphalt Mixture - Ullah, Rafi; Hafeez, Imran; Zaidi, Syed Bilal Ahmed; Jamal, Jamal; Haider, Safeer (Salehan Institute of Higher Education, 2020)
The major distresses in asphalt pavements are rutting, fatigue, and adhesion loss (moisture susceptibility). In this research study, two substitution fillers (Cement and Lime) were used with two different aggregate quarries (based on minerals composition) to evaluate the relatively most beneficial combination of both fillers as well as an aggregate quarry to enhance the performance life of asphalt pavements, especially in under-developed countries. Four basic tests, (Asphalt Pavement Analyzer, Four Points Bending Beam, Dynamic Modulus, and Rolling Bottle Test) that used for the most desired properties of any asphalt pavement, were utilized to access the performance properties of modified asphalt mixture. Based on all laboratory test results this research study concludes that replacement of aggregate filler with hydrated lime and cement has a beneficial effect on asphalt mix performance and to save investment by using raw material. Substitution filler improves the high-temperature rut performance and intermediate temperature fatigue performance of asphaltic concrete mixture up to 25% to that of the conventional mixture. At the same time, substitution filler has more beneficial to improve 70% adhesion properties to that of the conventional mixture.